Introduction: Silence after violence and the imperative to ‘speak out’ - Anja Henebury; Yehonatan Alsheh (Acta Academica, 2015)
From text: During the 1980s, a new dilemma emerged in various democratising nations, mostly in the global south: how should a repressive and violent past bedealt with in the context and as a constitutive part of democratisation?(Borneman 1997). The problem of the uses and abuses of the past instruggles over the public sphere has, of course, been around for centuries. The question arises: what was distinctly ‘new’ in this dilemma?